Multimilligram‐scale production implementation of atropisomers of 2, 2′‐bis(2, 2′‐bithiophene‐5‐yl)‐3, 3′‐bithianaphthene. Issue 4 (14th February 2021) - Rosetti, Alessia; Bonetti, Giorgia; Villani, Claudio; Benincori, Tiziana; Cirilli, Roberto
Abstract: 2, 2′‐Bis[2‐(5, 2′‐bithienyl)]‐3, 3′‐bithianaphthene (1 ) is the progenitor of a class of C 2 symmetric thiophene‐based electroactive monomers that, when electrooxidized in the enantiomerically pure form, produce inherently chiral films endowed with outstanding electrochemical enantiorecognition properties. The enantioselective high‐performance liquid chromatography (HPLC) is the only approach used so far to resolve the racemic form of 1 into enantiomers. In this work, an improved HPLC method for multimilligram enantiomer production is presented. Key factors controlling the enantioseparation, such as mobile phase composition and column temperature, were identified using a 100 × 4.6 mm i.d. Chiralpak IB‐3 column and subsequently scaled up to a 250 × 10.0 mm i.d. Chiralpak IB column. In the optimized semipreparative conditions, about 34 mg of pure (P ) and ( M ) enantiomers per hour could be produced. Abstract :